Fertilizer Loading Queue System Analysis at PT Meroke Tetap Jaya - Lijaya, Alwin; Johannes Ginting, Paris (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2021)
PT. Meroke Tetap Jaya is a company which operates in fertilizer distribution and has many warehouses across many areas. The problem often faced by this company is the occurrence of a very long queue and frequent loading overtime, which results in reduced customer satisfaction. To avoid long queue, it is necessary to determine the number of servers and workforces. This sparks an interest in the researcher to analyze a type of queuing system called Single Channel Multi Phase at the company’s warehouses. This research uses a queuing system method to analyze the amount and average time of queue as well as SPSS software to test the data distribution. Based on the results of the study, the calculation shows that the queue time for each truck is about 2 hours. To reduce the queuing time, consider increasing the number of workforces or modify the queuing system into Multi Channel Single Phase.